High-density Au nanoparticle loaded Au / CdS two-dimensional heterojunction as well as preparation method and application thereof

By loading high-density Au nanoparticles on the {0001} plane of the CdS heterojunction material, the Au/CdS two-dimensional heterojunction is formed, which solves the problem of unclear heterojunction interface structure and unused built-in electric field, and improves the photogenerated carrier separation efficiency and photocatalytic performance.

CN119746888APending Publication Date: 2025-04-04SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411801511.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The heterojunction interface structure in existing CdS heterojunction materials is unclear, and the built-in electric field is not fully utilized, resulting in low photogenerated carrier separation efficiency.

Method used

Using high-density Au/CdS two-dimensional heterojunction loaded by Au nanoparticles, Au nanoparticles are loaded on the {0001} plane of non-layered two-dimensional CdS material, the interface structure is clarified and the built-in electric field of the CdS crystal is fully utilized.

Benefits of technology

The separation efficiency and photocatalytic performance of photogenerated carriers are improved, and the heterojunction interface structure is clear and the built-in electric field is fully utilized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746888A_ABST
    Figure CN119746888A_ABST
Patent Text Reader

Abstract

The invention relates to the field of heterojunction material preparation, in particular to a high-density Au nanoparticle loaded Au / CdS two-dimensional heterojunction and a preparation method and application thereof. The Au / CdS two-dimensional heterojunction comprises a non-layered two-dimensional CdS material and Au nanoparticles loaded on a {0001} surface of the non-layered two-dimensional CdS material. In the Au / CdS two-dimensional heterojunction, Au nanoparticles are loaded on a {0001} crystal face (an electron gathering face) of a non-layered two-dimensional CdS material, the interface structure of the heterojunction is very clear, a built-in electric field in the CdS crystal can be more fully utilized, and the separation efficiency of photon-generated carriers is improved. Meanwhile, the invention further provides a preparation method of the Au / CdS two-dimensional heterojunction, and the method is simple and efficient and can be used for large-scale batch preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of heterojunction material preparation, and in particular to a high-density Au nanoparticle-loaded Au / CdS two-dimensional heterojunction and a preparation method and application thereof. Background Art

[0002] With the shortage of fossil energy and its adverse effects on the environment, developing methods to effectively utilize solar energy has become one of the major scientific challenges. Photocatalysis provides an ideal way to convert solar energy into sustainable and clean chemical fuels, such as photocatalytic decomposition of water to produce hydrogen. The essence of photocatalytic reaction is that semiconductors are excited by light and carriers are captured by adsorbed molecules, followed by further photochemical reactions. The separation of photogenerated carriers plays a decisive role in the efficiency of photocatalysis.

[0003] Constructing a built-in electric field in a photocatalyst is one of the most commonly used methods to improve the efficiency of photogenerated carrier separation. There are currently three main design ideas: one is to construct a heterojunction. When two different materials (at least one of the materials is a semiconductor) are in close contact, the energy band difference causes interface polarization, thereby generating a built-in electric field; the second is to introduce defects. The introduction of vacancies or impurity atoms in the semiconductor causes charge redistribution and generates a built-in electric field; the third is crystal plane engineering. Different crystal planes exposed on the surface of single-crystal semiconductor particles have different work functions, which leads to a built-in electric field between the crystal planes.

[0004] Among the widely studied heterojunction photocatalysts, cadmium sulfide (CdS) has attracted much attention due to its narrow band gap, visible light absorption ability and suitable conduction band position. Most of the existing CdS heterojunctions are based on spherical, one-dimensional rod-shaped or amorphous quantum dots. The growth of the heterojunction material on which CdS crystal plane is random, the heterojunction interface structure is unclear, and the mechanism of the built-in electric field of CdS itself is not clear and has not been fully utilized.

[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a high-density Au nanoparticle-loaded Au / CdS two-dimensional heterojunction and a preparation method and application thereof, aiming to solve the problems of unclear heterojunction interface structure and underutilized built-in electric field in existing CdS heterojunction materials.

[0007] The technical solution of the present invention is as follows:

[0008] In a first aspect of the present invention, a high-density Au nanoparticle-loaded Au / CdS two-dimensional heterojunction is provided, which includes a non-layered two-dimensional CdS material and Au nanoparticles loaded on the {0001} plane of the non-layered two-dimensional CdS material.

[0009] Optionally, the mass proportion of the Au nanoparticles in the Au / CdS two-dimensional heterojunction is 0.1%-50%.

[0010] Optionally, the thickness of the non-layered two-dimensional CdS material is 7 nm to 300 nm, and the thickness of the Au nanoparticles is 10 nm to 50 nm.

[0011] The second aspect of the present invention provides a method for preparing a high-density Au nanoparticle-loaded Au / CdS two-dimensional heterojunction, which comprises the steps of:

[0012] S1, providing a mica substrate on which a non-layered two-dimensional CdS material with a {0001} plane as an exposed surface is grown;

[0013] S2. Place the mica substrate in a mixed solution of water, methanol and H2AuCl4, and load Au nanoparticles on the {0001} surface of the non-layered two-dimensional CdS material under irradiation of a xenon lamp to obtain the high-density Au nanoparticle-loaded Au / CdS two-dimensional heterojunction.

[0014] Optionally, the volume ratio of water, methanol and H2AuCl4 is (20-40) mL: (5-10) mL: (10-2000) μL.

[0015] Optionally, step S1 specifically includes:

[0016] S10, providing a reaction container, and dividing the reaction container into an upstream area, a central heating area, and a downstream area;

[0017] S11, In2S3 powder is used as a passivating agent and placed in the central heating area of ​​the reaction vessel, Zn 0.5 Cd 0.5 S powder and sulfur powder are used as raw materials and placed in the upstream area of ​​the reaction container, and the mica substrate is placed in the downstream area of ​​the reaction container;

[0018] S12. A temperature rising program is set for the central heating area of ​​the reaction container to heat up to 900°C to 1000°C at a rate of 20°C / min to 40°C / min and then keep warm for 10min to 40min, and at the same time, an inert gas is introduced into the reaction container, wherein the inert gas flows from the upstream area to the downstream area, so as to obtain a mica substrate with a non-layered two-dimensional CdS material with the {0001} plane as the exposed surface grown on the surface.

[0019] Optionally, the Zn 0.5 Cd 0.5The mass ratio of S powder, sulfur powder and In2S3 powder is (2~10) mg: (2~20) mg: (10~40) mg.

[0020] Optionally, the distance between the upstream region and the central heating region is 10 cm to 20 cm, and the distance between the downstream region and the central heating region is 10 cm to 20 cm.

[0021] Optionally, the inert gas is argon, and the flow rate of the inert gas is 60 sccm to 300 sccm.

[0022] The third aspect of the present invention provides an application of the Au / CdS two-dimensional heterojunction loaded with high-density Au nanoparticles as described in the present invention in a photocatalytic reaction.

[0023] Beneficial effects: The present invention provides a high-density Au nanoparticle-loaded Au / CdS two-dimensional heterojunction, wherein the Au nanoparticles are loaded on the {0001} crystal plane (electron gathering plane) of the non-layered two-dimensional CdS material, and the interface structure of the heterojunction is very clear, which can make full use of the built-in electric field in the CdS crystal and improve the separation efficiency of photogenerated carriers. A method for preparing the Au / CdS two-dimensional heterojunction is also provided, which is simple and efficient and can be used for large-scale batch preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is an optical microscope photograph of the non-layered two-dimensional CdS material prepared in step 2 of Example 1.

[0025] Figure 2 It is the AFM image and corresponding thickness curve of the non-layered two-dimensional CdS material obtained in step 2 of Example 1 and the Au / CdS two-dimensional heterojunction material obtained in step 3.

[0026] Figure 3 This is the HRTEM image of the non-layered two-dimensional CdS material prepared in step 2 of Example 1.

[0027] Figure 4 The low-magnification HAADF-STEM image and elemental surface scanning image of the cross section of the Au / CdS two-dimensional heterojunction material obtained in step three of Example 1.

[0028] Figure 5 It is the surface potential diagram and corresponding potential curve of the non-layered two-dimensional CdS material obtained in step 2 of Example 1 and the Au / CdS two-dimensional heterojunction material obtained in step 3 under dark and light conditions.

[0029] Figure 6It is a graph showing the transient absorption spectra of the non-layered two-dimensional CdS material obtained in step 2 of Example 1 and the Au / CdS two-dimensional heterojunction material obtained in step 3, and the relationship between the bleaching signal intensity at 500 nm and time.

[0030] Figure 7 3 are AFM images of the Au surface of the Au / CdS two-dimensional heterojunctions with different Au thicknesses prepared in Example 1 and Example 2. DETAILED DESCRIPTION

[0031] The present invention provides a high-density Au nanoparticle-loaded Au / CdS two-dimensional heterojunction and a preparation method and application thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0032] An embodiment of the present invention provides a high-density Au nanoparticle-loaded Au / CdS two-dimensional heterojunction, which includes a non-layered two-dimensional CdS material and Au nanoparticles loaded on the {0001} plane of the non-layered two-dimensional CdS material.

[0033] The high-density Au nanoparticle-loaded Au / CdS two-dimensional heterojunction provided in an embodiment of the present invention comprises a non-layered two-dimensional CdS material having a hexagonal wurtzite structure with the {0001} crystal plane exposed. The non-layered two-dimensional CdS material is bonded by strong chemical bonds in the three-dimensional spatial directions, and it is difficult to grow a heterojunction in one dimension. The two-dimensional CdS material in the embodiment of the present invention adopts a CdS crystal in a wurtzite structure, and there is a built-in electric field along the {0001} direction of the crystal inside the crystal. Based on such a two-dimensional CdS material, Au can grow completely on the {0001} plane (electron aggregation plane) of CdS. In this way, the interface structure of the heterojunction is very clear, and the built-in electric field of CdS can be more fully utilized to improve the carrier separation efficiency.

[0034] In one embodiment, the mass proportion of the Au nanoparticles in the Au / CdS two-dimensional heterojunction loaded with high-density Au nanoparticles is 0.1%-50%.

[0035] In one embodiment, the thickness of the non-layered two-dimensional CdS material is 7nm to 300nm, preferably 7nm to 100nm, more preferably 10nm to 40nm, for example, 10nm, 17nm, 20nm, 25nm, 30nm, 35nm or 40nm.

[0036] In one embodiment, the Au nanoparticles have a thickness of 10 nm to 50 nm, for example, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm.

[0037] The embodiment of the present invention provides a method for preparing an Au / CdS two-dimensional heterojunction, which comprises the following steps:

[0038] S1, providing a mica substrate on which a non-layered two-dimensional CdS material with a {0001} plane as an exposed surface is grown;

[0039] S2. Place the mica substrate in a mixed solution of water, methanol and H2AuCl4, and load Au nanoparticles on the {0001} surface of the non-layered two-dimensional CdS material under irradiation of a xenon lamp to obtain the high-density Au nanoparticle-loaded Au / CdS two-dimensional heterojunction.

[0040] In an embodiment of the present invention, a mica substrate with a non-layered two-dimensional CdS material grown on the surface is first provided, wherein the exposed surface of the two-dimensional CdS material is a {0001} crystal plane (electron gathering plane), and then metal Au nanoparticles are loaded on the surface of the non-layered two-dimensional CdS material to obtain an Au / CdS two-dimensional heterojunction. The preparation method provided by the present invention is simple and efficient and can be used for large-scale batch preparation.

[0041] The substrate in the embodiment of the present invention can only be a mica substrate. Other substrates commonly used in the prior art, such as a quartz substrate, a silicon wafer, etc., cannot obtain a non-layered two-dimensional CdS material.

[0042] In step S1, in some implementations, step S1 specifically includes:

[0043] S10, providing a reaction container, and dividing the reaction container into an upstream area, a central heating area, and a downstream area;

[0044] S11, In2S3 powder is used as a passivating agent and placed in the central heating area of ​​the reaction vessel, Zn 0.5 Cd 0.5 S powder and sulfur powder are used as raw materials and placed in the upstream area of ​​the reaction container, and the mica substrate is placed in the downstream area of ​​the reaction container;

[0045] S12. Set a temperature rising program for the central heating area of ​​the reaction container to heat up to 900°C~1000°C (preferably 930°C) at a rate of 20°C / min~40°C / min (preferably 30°C / min), and then keep warm for 10min~40min (preferably 30min), and at the same time, introduce an inert gas into the reaction container, wherein the inert gas flows from the upstream area to the downstream area, so as to obtain a mica substrate with a non-layered two-dimensional CdS material with the {0001} plane as the exposed surface grown on the surface.

[0046] In some embodiments, the reaction container is a quartz tube.

[0047] In some embodiments, the Zn 0.5 Cd 0.5 The mass ratio of S powder, sulfur powder and In2S3 powder is (2-10) mg: (2-20) mg: (10-40) mg; preferably, the Zn 0.5 Cd 0.5 The mass ratio of S powder, sulfur powder and In2S3 powder is 5mg:20mg:10mg.

[0048] In some embodiments, the distance between the upstream region and the central heating region is 10 cm to 20 cm, and the distance between the downstream region and the central heating region is 10 cm to 20 cm.

[0049] In some embodiments, the inert gas is argon, and the flow rate of the inert gas is 60-300 sccm.

[0050] In some embodiments, the Zn 0.5 Cd 0.5 The preparation method of S powder adopts a solvent thermal method, which specifically includes the steps of:

[0051] S20, dissolving cadmium acetate and zinc acetate in a first solvent to obtain a first solution, and dissolving sodium sulfide in a second solvent to obtain a second solution;

[0052] S21, slowly dropwise adding the second solution to the first solution, then adding alkali, stirring, ultrasonicating and heating the solution, and finally washing and drying the solution to obtain the Zn 0.5 Cd 0.5 S.

[0053] In some embodiments, the molar ratio of cadmium acetate, zinc acetate and sodium sulfide is 1:1:4.

[0054] In some embodiments, the first solvent and the second solvent are ethylene glycol, and the base is ethylenediamine.

[0055] In some embodiments, in step S21, the temperature of the heating reaction is 160 to 220° C., and the time of the heating reaction is 12 to 60 hours.

[0056] In some embodiments, in step S21, the washing liquid used in the washing process is deionized water and anhydrous ethanol.

[0057] In some embodiments, in step S21, the temperature of the drying process is 60 to 120°C, and the time of the drying process is 12 to 24 hours.

[0058] In step S2, in some embodiments, the volume ratio of water, methanol and H2AuCl4 is (20-40) mL: (5-10) mL: (10-2000) μL; preferably, the volume ratio of water, methanol and H2AuCl4 is 40 mL: 10 mL: 1000 μL.

[0059] In some embodiments, the xenon lamp irradiation time is 10 to 20 minutes.

[0060] In some embodiments, the concentration of H2AuCL4 is 0.001M.

[0061] In some implementations, step S2 specifically includes:

[0062] The mica substrate is placed in a mixed solution of water, methanol and H2AuCL4, and after vacuuming, introducing argon gas and irradiating with a xenon lamp, Au nanoparticles are loaded on the {0001} surface of the non-layered two-dimensional CdS material to obtain the Au / CdS two-dimensional heterojunction.

[0063] An embodiment of the present invention provides an application of the Au / CdS two-dimensional heterojunction as described in the present invention in a photocatalytic reaction.

[0064] The present invention will be further described below by means of specific examples.

[0065] Example 1

[0066] This embodiment provides a method for preparing an Au / CdS two-dimensional heterojunction, which is as follows:

[0067] Step 1: Preparation of Zn using a solvothermal method 0.5 Cd 0.5 S powder:

[0068] Weigh 0.5mmol of cadmium acetate and 0.5mmol of zinc acetate and dissolve them in a polytetrafluoroethylene liner containing 10mL of ethylene glycol. Weigh 2mmol of sodium sulfide and dissolve it in 10mL of ethylene glycol, and slowly drip it into the mixed solution of cadmium acetate and zinc acetate (average 1 drop / second). After adding 40mL of ethylenediamine to the above solution, cover the liner with a polytetrafluoroethylene lid, stir vigorously with a magnetic bar for 1h, remove the magnetic bar and put it into an ultrasonic tank for ultrasonic treatment for 1h. Put the polytetrafluoroethylene liner into a stainless steel reactor, tighten it and put it into a constant temperature drying oven, and react at 220℃ for 48h. After the reaction is completed, cool it naturally to room temperature, wash the obtained product with deionized water and anhydrous ethanol 4 to 5 times, and dry it at 60℃ for 12h to finally obtain Zn 0.5 Cd 0.5 S powder.

[0069] Step 2: Prepare a mica substrate with a non-layered two-dimensional CdS material with the {0001} surface as the exposed surface grown on the surface:

[0070] Weigh 5 mg of Zn obtained in step 1 0.5 Cd 0.5 S powder, 20 mg of S powder and 10 mg of In2S3 powder, and put them into the cleaned quartz boat respectively; tear off the two outer layers of the upper and lower surfaces of the mica sheet with gold finger tape to obtain a mica sheet with a clean surface.

[0071] The weighed In2S3 powder was used as a passivating agent and placed in the central heating area of ​​the quartz tube. 0.5 Cd 0.5 S powder and S powder are used as raw materials and are placed separately in the upstream area 10 cm away from the central heating area of ​​the quartz tube, and the surface-cleaned mica sheet is placed in the downstream area 10 cm away from the central heating area of ​​the quartz tube;

[0072] Repeatedly evacuate and fill with argon three times with a mechanical pump to remove as much residual air as possible from the quartz tube;

[0073] The central heating area of ​​the quartz tube (the length of the heating area is 20 cm) was set to a temperature program: the temperature was raised to 930°C at a rate of 30°C / min and then kept at this temperature for 30 minutes, and argon was introduced into the quartz tube at the same time, and the argon flow direction was from the upstream area to the downstream area. After the reaction was completed, it was naturally cooled to room temperature to obtain a mica sheet with a non-layered two-dimensional CdS material with the {0001} surface as the exposed surface grown on the surface.

[0074] Step 3: Preparation of Au / CdS two-dimensional heterojunction:

[0075] The mica sheet obtained in step 2 was placed in a sealed quartz container containing 40 mL of deionized water, 10 mL of methanol and 1000 uL of a 0.001 M H2AuCl4 mixed solution. The air in the solution was expelled by vacuum for 10 min, and then argon gas was introduced into the solution. Finally, the solution was irradiated under a xenon lamp for 10 min. Au nanoparticles were loaded on the {0001} surface of the non-layered two-dimensional CdS material, and finally an Au / CdS two-dimensional heterojunction was obtained.

[0076] Figure 1 This is an optical microscope photograph of the non-layered two-dimensional CdS material prepared in step 2. Figure 2 are atomic force microscope (AFM) images of the non-layered two-dimensional CdS material obtained in step 2 and the Au / CdS two-dimensional heterojunction material obtained in step 3 and the corresponding thickness curves, wherein a) is the AFM image of the non-layered two-dimensional CdS material, Figure 2 b) in the figure is the thickness curve corresponding to the white line in figure a), and it can be seen that its thickness is about 30nm. Figure 2 Figure c) is an AFM image of the Au / CdS two-dimensional heterojunction. Figure 2 d) in the figure is the thickness curve corresponding to the white line in c). It can be seen that its thickness is about 80nm, which means that the thickness of the material increases by 50nm after loading Au nanoparticles, and the thickness of Au nanoparticles is 50nm. In addition, Figure 2 c) The large white dots in the figure indicate areas with relatively high thickness.

[0077] Figure 3 It is the Fourier transform image corresponding to the high-resolution projection electron microscopy (HRTEM) photograph of the non-layered two-dimensional CdS material prepared in step 2. The HRTEM image shows that the non-layered two-dimensional CdS material has perfect lattice fringes, and the interplanar spacing of 0.36nm corresponds to the {1010} crystal plane of the hexagonal CdS crystal. The diffraction spots are clear and sharp, which further proves that the synthesis has obtained high-quality surface-grown non-layered two-dimensional CdS material with the {0001} crystal plane as the exposed surface.

[0078] Figure 4 This is the low-magnification HAADF-STEM (high-angle annular dark field scanning transmission) image and elemental surface scanning image of the cross section of the Au / CdS two-dimensional heterojunction material obtained in step 3. The image shows that CdS and Au have a very clear interface, and the elemental surface scanning image of the cross section shows that Au elements and Cd and S elements are very evenly distributed in two areas. This result shows that Au grows on the CdS surface, forming a heterojunction structure with a very clear interface structure.

[0079] In addition, the surface potential of the non-layered two-dimensional CdS material obtained in step 2 and the Au / CdS two-dimensional heterojunction material obtained in step 3 under dark and light conditions was tested. The specific method was to use an atomic force microscope (Bruker, model Dimension Edge) to image the surface morphology and surface potential of the samples, respectively. A Pt / Ir-wrapped Si conductive probe (SCM-PIT-V2) was used, with a force constant of 1-5N / m and a resonance frequency of 72kHz. The test process first used the tapping mode to scan the surface morphology of the sample, and then the lift mode was used to lift the sample to a certain height (30nm) and scan the surface potential of the sample. The scanning rate was 0.6Hz, and each image contained 256×256 data points.

[0080] Figure 5 is the surface potential diagram and corresponding potential curve of the non-layered two-dimensional CdS material obtained in step 2 and the Au / CdS two-dimensional heterojunction material obtained in step 3 under dark and light conditions, wherein Figure 5 Figure a) is the surface potential diagram of non-layered two-dimensional CdS material under dark conditions. Figure 5 Figure b) is the surface potential diagram of non-layered two-dimensional CdS material under light conditions. Figure 5 Figure c) is the corresponding potential curve of non-layered two-dimensional CdS material under dark and light conditions. Figure 5 Figure d) is the surface potential diagram of Au / CdS two-dimensional heterojunction material under dark conditions. Figure 5 Figure e) is the surface potential diagram of Au / CdS two-dimensional heterojunction material under light conditions. Figure 5 Figure f) is the corresponding potential curve of Au / CdS two-dimensional heterojunction material under dark and light conditions. The results show that the surface potential difference (38 mV) of Au / CdS two-dimensional heterojunction material under light and dark conditions is significantly greater than that of pure two-dimensional CdS material (21 mV), which indicates that the charge separation efficiency of Au / CdS two-dimensional heterojunction material is significantly better than that of pure two-dimensional CdS material.

[0081] Figure 6 The transient absorption spectra of the non-layered two-dimensional CdS material obtained in step 2 of Example 1 and the Au / CdS two-dimensional heterojunction material obtained in step 3 and the relationship between the bleaching signal intensity at 500 nm and time are shown. Figure 6 Figures a) and b) are the transient absorption spectra of the non-layered two-dimensional CdS material obtained in step 2 and the Au / CdS two-dimensional heterojunction material obtained in step 3 in 10% methanol solution, respectively. It can be seen that the negative signal near 500nm is the ground state bleaching signal of CdS. Figure 6Figure c) is a graph showing the time evolution of the intensity of the ground state bleaching signal of the non-layered two-dimensional CdS material obtained in step 2 and the Au / CdS two-dimensional heterojunction material obtained in step 3. The results show that the decay of the ground state bleaching signal in the Au / CdS two-dimensional heterojunction material with time is significantly faster than that of the pure two-dimensional CdS material, which indicates that the charge separation efficiency in the Au / CdS two-dimensional heterojunction material is significantly better than that of the pure two-dimensional CdS material.

[0082] Example 2

[0083] The preparation method is the same as that of Example 1, except that the amount of H2AuCl4 in step three is adjusted to 100uL, 30uL and 10uL, respectively, thereby preparing Au / CdS two-dimensional heterojunctions with Au thicknesses of 40nm, 15nm and 10nm, respectively.

[0084] Figure 7 is an AFM image of the Au surface of the Au / CdS two-dimensional heterojunction with different Au thicknesses prepared in Example 1 and Example 2, wherein Figure 7 The thickness of Au in the figure a) is 50nm. Figure 7 The thickness of Au in Figure b) is 40nm. Figure 7 The thickness of Au in Figure c) is 15nm. Figure 7 The thickness of Au in Figure d) is 10 nm.

[0085] In summary, the present invention successfully prepared an Au / CdS two-dimensional heterojunction loaded with high-density Au nanoparticles. The Au nanoparticles were loaded on the {0001} crystal plane of the non-layered two-dimensional CdS material. The interface structure of the heterojunction was very clear, which could make more full use of the built-in electric field in the CdS crystal, thereby improving the separation efficiency of photogenerated carriers and the photocatalytic performance.

[0086] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A high-density Au nanoparticle-loaded Au / CdS two-dimensional heterojunction, characterized in that: The invention comprises a non-layered two-dimensional CdS material and Au nanoparticles loaded on the {0001} surface of the non-layered two-dimensional CdS material.

2. The Au / CdS two-dimensional heterojunction loaded with high-density Au nanoparticles according to claim 1, characterized in that: The mass proportion of the Au nanoparticles in the Au / CdS two-dimensional heterojunction is 0.1%-50%.

3. The Au / CdS two-dimensional heterojunction loaded with high-density Au nanoparticles according to claim 1, characterized in that: The thickness of the non-layered two-dimensional CdS material is 7nm to 300nm, and the thickness of the Au nanoparticles is 10nm to 50nm.

4. A method for preparing a high-density Au nanoparticle-loaded Au / CdS two-dimensional heterojunction as claimed in claim 1, characterized in that: Includes steps: S1, providing a mica substrate on which a non-layered two-dimensional CdS material with a {0001} plane as an exposed surface is grown; S2. Place the mica substrate in a mixed solution of water, methanol and H2AuCl4, and load Au nanoparticles on the {0001} surface of the non-layered two-dimensional CdS material under irradiation of a xenon lamp to obtain the high-density Au nanoparticle-loaded Au / CdS two-dimensional heterojunction.

5. The method for preparing the Au / CdS two-dimensional heterojunction loaded with high-density Au nanoparticles according to claim 4, characterized in that: The volume ratio of the water, methanol and H2AuCl4 is (20-40) mL: (5-10) mL: (10-2000) μL.

6. The method for preparing the Au / CdS two-dimensional heterojunction loaded with high-density Au nanoparticles according to claim 4, characterized in that: Step S1 specifically includes: S10, providing a reaction container, and dividing the reaction container into an upstream area, a central heating area, and a downstream area; S11, In2S3 powder is used as a passivating agent and placed in the central heating area of ​​the reaction vessel, Zn 0.5 Cd 0.5 S powder and sulfur powder are used as raw materials and placed in the upstream area of ​​the reaction container, and the mica substrate is placed in the downstream area of ​​the reaction container; S12. A temperature rising program is set for the central heating area of ​​the reaction container to heat up to 900°C to 1000°C at a rate of 20°C / min to 40°C / min and then keep warm for 10min to 40min, and at the same time, an inert gas is introduced into the reaction container, wherein the inert gas flows from the upstream area to the downstream area, so as to obtain a mica substrate with a non-layered two-dimensional CdS material with the {0001} plane as the exposed surface grown on the surface.

7. The method for preparing the Au / CdS two-dimensional heterojunction loaded with high-density Au nanoparticles according to claim 6, characterized in that: The Zn 0.5 Cd 0.5 The mass ratio of S powder, sulfur powder and In2S3 powder is (2~10) mg: (2~20) mg: (10~40) mg.

8. The method for preparing the Au / CdS two-dimensional heterojunction loaded with high-density Au nanoparticles according to claim 6, characterized in that: The distance between the upstream area and the central heating area is 10 cm to 20 cm, and the distance between the downstream area and the central heating area is 10 cm to 20 cm.

9. The method for preparing the Au / CdS two-dimensional heterojunction loaded with high-density Au nanoparticles according to claim 6, characterized in that: The inert gas is argon gas, and the flow rate of the inert gas is 60 sccm to 300 sccm.

10. Use of the Au / CdS two-dimensional heterojunction loaded with high-density Au nanoparticles as claimed in claim 1 in a photocatalytic reaction.